Sex- and age-related differences in half-marathon performance and competitiveness in the world's largest half-marathon – the GöteborgsVarvet. Issue 1 (2nd January 2018) - Knechtle, B.; Nikolaidis, PT
ABSTRACT: In road runners, the age-related performance decline has been well investigated for marathoners, but little is known for half-marathoners. We analysed data from 138, 616 runners (48, 148 women and 90, 469 men) competing between 2014 and 2016 in GöteborgsVarvet, the world's largest half-marathon. The men-to-women ratio in participants increased with age, the fastest race times were observed in age groups ˂35 and 35–39 years in women and in age group 35–39 years in men, the main effect of sex and the sex × age group interaction on race time were trivial, and the competitiveness was denser in men and in the younger age groups. In summary, in half-marathon running in the largest half-marathon in the world, the GöteborgsVarvet, women achieved the fastest race time at an earlier age compared to men where the fastest race times were observed in women in age groups ˂35 and 35–39 years and in men in age group 35–39 years.